2018
DOI: 10.1161/jaha.117.007555
|View full text |Cite
|
Sign up to set email alerts
|

Sp1 Plays an Important Role in Vascular Calcification Both In Vivo and In Vitro

Abstract: BackgroundVascular calcification and increased cardiovascular morbidity and mortality are closely related in patients with end‐stage renal disease and diabetes mellitus. Specific protein 1 (Sp1) is a transactivation molecule that plays a crucial role in the regulation of apoptosis, fibrosis, angiogenesis, and other pathological disorders. There is evidence that specific protein 1 (Sp1) directly stimulates the transcription of bone morphogenetic protein 2 (BMP2) and that BMP2 plays a key role in the calcificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…Diabetes-induced vascular complication was associated with phenotypic modulation of VSMCs, switching from a contractile to a synthetic-proliferative phenotype [1]. In the preliminary study, we confirmed that 25mM glucose could induce the phenotypic switching of VSMCs and showed no significant effects in cell viability.…”
Section: Pge1 Reversed the Phenotypic Switching Of Vsmcssupporting
confidence: 62%
See 1 more Smart Citation
“…Diabetes-induced vascular complication was associated with phenotypic modulation of VSMCs, switching from a contractile to a synthetic-proliferative phenotype [1]. In the preliminary study, we confirmed that 25mM glucose could induce the phenotypic switching of VSMCs and showed no significant effects in cell viability.…”
Section: Pge1 Reversed the Phenotypic Switching Of Vsmcssupporting
confidence: 62%
“…VSMCs undergo phenotype switching in T2DM patients or diabetic rats, which might be associated with the onset or progression of atherogenic process [1]. However, the underlying molecular mechanisms mediating phenotypic change of VSMCs remain not entirely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the effect of bioactive compounds (BC) on this transcription factor showed that orientin, isoorientin, vitexin, and isovitexin exert suppressive action of these compounds upon NF-κB activation [24]. Elevated SP1 plays a pro-apoptotic effect and stimulates vascular calcification [83]. It has been observed that the BC (-)-epigallocatechin-3-gallate can modulate the activity of this transcription factor [84].…”
Section: Discussionmentioning
confidence: 99%
“…Specificity Protein 1 (Sp1) is a key transcription factor involved in several biological pathways, acting as positive or negative gene expression regulator; in particular it plays a critical role in cell proliferation, cell cycle progression and apoptosis [29][30][31]. Emerging studies report a role of Sp1 in OB differentiation; in fact, its downregulation prevents vascular calcification by inhibiting the transdifferentiation of vascular smooth muscle cells into OBs [32]. In addition, Sp1 increases the mineralization of osteoblastic cells [33].…”
Section: Introductionmentioning
confidence: 99%